Manajemen Program Pengembangan dalam Meningkatkan Kompetensi Guru di MTS Al Azhar Guluk Manjung Kecamatan Bluto Sumenep - Sulaiha Sulaiha; Hasyim Asy’ari; Ashari Ashari (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
Based on the research findings, the pedagogical competence of teachers at MTs Al Azhar Guluk Manjung Bluto Sub-district Sumenep is relatively good. This is evident through pre-teaching planning, understanding students' characteristics and psychology, mastering teaching materials, utilizing Information and Communication Technology (ICT), and updating teaching materials. Teachers also participate in various specialized training related to teacher competence development, adapt their educational backgrounds to their subjects, present tutorials with student-friendly teaching methods, consult literature related to specific subjects, review test questions before administering them to students, and apply teaching methods suitable for each subject, such as lectures, question-and-answer sessions, and discussions. Regular meetings are held at the beginning of the semester, and evaluations are conducted every three to six months. The implementation of Pedagogical Competence of Teachers at MTs Al Azhar Guluk Manjung Bluto Sub-district Sumenep is at a relatively good level but requires refinement. Challenges faced in implementing pedagogical competence include limited facilities, resources, and limited operational education budget. The solutions to overcome these challenges include utilizing available facilities.